Mitochondrial scenario: roles of mitochondrial dynamics in acute myocardial ischemia/reperfusion injury. (2nd January 2021) - Mui, David; Zhang, Ying
Abstract: The main therapeutic strategy currently used for acute myocardial infarction (AMI) is to open occluded coronary arteries, a process defined as blood reperfusion. However, blood reperfusion will increase cardiac mortality, tissue damage and cardiac dysfunction in patients with AMI, which is mechanically defined as "ischemia/reperfusion (I/R) injury". It is currently believed that mitochondrial dynamics plays a key role in myocardial I/R, especially excessive mitochondrial fission, which is the main cause of cardiac dysfunction. Therefore, in the process of I/R injury, effective drug intervention and correct treatment strategies can be used to regulate mitochondrial dynamic balance to combat ischemia-reperfusion injury, which can play a huge role in improving the prognosis of patients. This review summarized the effects of mitochondrial fission and mitochondrial fusion balance on myocardial and mitochondrial functional changes during myocardial I/R injury. Finally, combined with the previous injury mechanisms, this review also briefly described some drug intervention that may be beneficial to clinical practice to improve the postoperative quality of life of patients with AMI.